2012
DOI: 10.1021/jp304079b
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects on Water Clusters Inside Carbon Nanotubes

Abstract: The effects of confinement on water clusters inside nonmetallic carbon nanotubes with radii ranging between 4 and 7.5 Å have been computationally investigated by means of global optimization and finite temperature simulations. The water−water interaction is described by the TIP4P rigid body potential, and a Lennard-Jones potential is used for the water− carbon interaction. Water clusters containing up to 20 molecules are found to form 1D chainlike configurations for the narrow (7, 5) nanotube and 2D ladderlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 81 publications
(187 reference statements)
2
59
0
Order By: Relevance
“…Global minima were obtained using the BH 62 or Monte Carlo (MC) minimization 63 method, successfully employed before for both neutral 62,64,65 and charged atomic and molecular clusters [66][67][68][69][70][71] , along with many other applications. 72 This technique is a stochastic method that involves perturbation followed by minimization at each step.…”
Section: Basin-hopping Methodsmentioning
confidence: 99%
“…Global minima were obtained using the BH 62 or Monte Carlo (MC) minimization 63 method, successfully employed before for both neutral 62,64,65 and charged atomic and molecular clusters [66][67][68][69][70][71] , along with many other applications. 72 This technique is a stochastic method that involves perturbation followed by minimization at each step.…”
Section: Basin-hopping Methodsmentioning
confidence: 99%
“…This technique has been used successfully for both neutral [32,39,40] and charged atomic and molecular clusters [41][42][43][44][45][46], along with many other applications. [47] In the size range considered here the global optimization problem is feasible at a reasonable computational cost.…”
Section: B Bh Minimizationmentioning
confidence: 99%
“…Particular attention was paid to the signatures in these vibrational spectra and the important role of hydrogen bonds in determining the structural, electronic, and spectral properties of INTs. Figure 6 depicts the optimized pentagonal, hexagonal, and heptagonal INTs with confinement in the cylindrical hollow spaces of zigzag (15, 0), (16,0), and (17, 0) SWCNTs. Our calculations shown that water molecules can form ordered cylindrical crystalline structures, referred to as INTs, by formation of perfect hydrogen bonding under confinement within SWCNTs.…”
Section: Ice Nanotubes (Ints) Confined In Swcntsmentioning
confidence: 99%
“…When water is adsorbed on the substrates, it will minimize its energy by adopting a specific structure to that surface, and that the geometry is dependent on the relative strength of the water-surface interaction and the water-water interaction. In the past two decades, the interactions of water molecules with various graphitic materials, including graphene, carbon nanotubes, and graphite, have attracted wide spread attention among experimental and computational chemists [4][5][6][7][8][9][10][11][12][13][14][15][16]. The understanding of the water interactions with graphenes or single walled carbon nanotubes (SWCNTs) is very important for potential applications of these materials.…”
Section: Introductionmentioning
confidence: 99%